PRACTICAL REALIZATION OF POWER AND DATA TRANSFER USING WPT SYSTEMS - Murat, Anel (Nazarbayev University School of Engineering and Digital Sciences, 2025)
This project presents the design of a compact defected ground structure (DGS)-based wireless power transfer (WPT) system with dual-band functionality, developed for biomedical applications. The first system is specifically optimized to achieve high power transfer efficiency. The development begins with the design of a dual-band resonator with a size of 15-by-15 sq. mm., optimized to ensure optimal current distribution. Wireless power transfer is then realized by coupling two such resonators at a 10 mm transmission range. The system achieves a power transfer efficiency of 79% at 0.9 GHz and 60.5% at 1.8 GHz. To assess practical viability, the system’s performance is evaluated under displacement conditions, demonstrating stable operation within a specific range of horizontal and vertical misalignments. Building on these results, the second part of the project focuses on implementing a wireless information and power transfer (WIPT) system, followed by an experimental evaluation of its performance in both power and data transmission. Two resonators with distinct defects and different operating frequencies are designed and connected in series to form a dual-band resonator with a final size of 18-by-18 sq. mm., operating at 433 MHz and 900 MHz. Two identical resonators are then coupled at a 15 mm separation distance to form the WIPT system, which achieves power transfer efficiencies of 53.9% at 433 MHz and 54.7% at 900 MHz. Data transmission performance is evaluated based on bit error rate (BER) using a Universal Software Radio Peripheral (USRP) configured through LabVIEW. BER is measured at varying separation distances, reaching minimum values of 0.0318 at 433 MHz and 0.0197 at 900 MHz under perfect alignment conditions. Furthermore, text data is transmitted using the WIPT system and analyzed through constellation plots, which show clearly defined and symmetrically arranged points, indicating accurate and stable data transmission.
Keywords: Bit-error-rate (BER); biomedical applications; constellation diagram; defected ground structure (DGS); dual-band resonator; electromagnetic coupling; figure of merit (FoM); industrial; scientific; and medical (ISM) band; LabVIEW; near-field coupling; power transfer efficiency; resonator coupling; universal software radio peripheral (USRP); wireless information and power transfer (WIPT); wireless power transfer (WPT); type of access: open access